ANALISIS ALIH FUNGSI LAHAN PADI MENJADI LAHAN SAWIT DI DESA KEMUNING MUDA KECAMATAN BUNGA RAYA KABUPATEN SIAK - Ramli "; Syamsul Bahri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
The change of land type is to increase the land-use type in one sector followed to other sectors by the reduction of land types. By the other word, the land-use change is the change of land function in a particular period of time, as such the changes of agricultural land that used for non-agricultural land. The aim of this study is to investigate and analyze the conditions of farming business society in Kemuning Muda Village of Bunga Raya sub-district in Siak Regency as well as to investigate and analyze the factors that affect farmers to make the conversion of the paddy land to oil palm land in Kemuning Muda Village of Bunga Raya sub-district in Siak Regency. This study is expected to be as inputs and sources of thought for other studies in deeper investigation of the land conversion issues. This study was occurring at the beginning to end of January. The quantitative descriptive study methodology was employed to find out and describe the particular social phenomenon and attempt to analyze it appropriately with the fact based on collecting data. The types of data used were primary and secondary data. The data collection techniques were using questionnaires and documentation. Descriptive quantitative methods was used for data analysis, first the authors frame the data into a table and then briefed and analyzed descriptively. The results showed that the data presentation of this study described based on data gathered from field research which includes a variety of farmer’s characteristics may include demographic character, social character and the character of the economic condition of the farmers themselves. These characters differentiate the type of farmer behavior in certain circumstances. Characteristics observed in this study were age, education, the number of dependents, employment, land area, income. The factors influencing farmers to conversion of land-use were social change in the farmer groups community wherein bring the change of social and economic conditions around him both internally and externally. Keywords: conversion, land, social